The Early Jesuits’ Transformative Vision of Education in the Context of Colonization from Their Sixteenth-Century Beginnings to Their Suppression in 1773: A Longue Durée Synthesis and Online Interactive Map Locating the Colleges - Rosa Bruno-Jofré; Ana Jofre (Cadernos de História da Educação)
This paper comprises two parts, a longue durée interpretative historical synthesis that examines the Jesuits’ transformative vision of education, and a digital interactive map that visualizes the globality of their educational enterprise (https://theirgroup.org/Jesuits/map/). The Jesuits’ vision of education, grounded in humanism, and its intersection with confessionalization, as well as their aim to generate a secular Catholic leadership are placed within the developing geopolitical context of coloniality and in interplay with micro and macro political, social, economic, and religious contexts. Special attention is paid to the interaction with the emerging configurations of modern ideas, particularly those developed in the sixteenth and seventeenth centuries. The historiography of the last two decades is referred to in the analysis of how the Jesuits related to emerging ecologies of knowledge and to the limits to their articulation with those knowledges.